Adsorptive behaviour of palm oil mill sludge biochar pyrolyzed at low temperature for copper and cadmium removal. (1st May 2019) - Goh, Ching Lam; Sethupathi, Sumathi; Bashir, Mohammed JK.; Ahmed, Waseem
Abstract: In this work, the influence of pyrolysis temperature on the physicochemical properties of palm oil mill sludge biochar (POSB) and its adsorption properties towards cadmium (Cd) and copper (Cu) was investigated. Characterization experiments suggested that POSBs' surface functional groups play the major role in the adsorption process. POSB pyrolyzed at 400 °C showed the best characteristics for Cu and Cd removal. Adsorption study indicated that contact time and shaking speed enhances the adsorption capacity of POSB. It was affirmed that pH adjustment is not necessary for POSB to adsorb Cu and Cd. Mechanism studies fitted well with Langmuir and Pseudo-Second Order model. Thermodynamic parameters indicated that the adsorption was spontaneous, endothermic and correspond to chemical adsorption. The highest uptakes of Cu and Cd were recorded at 48.8 mg/g and 46.2 mg/g respectively. This work verifies that the temperature used for palm oil mill sludge (POS) pyrolysis and adsorption condition played the most prominent role in Cu and Cd removal from aqueous solutions. Highlights: Optimized palm oil mill sludge biochar for copper and cadmium removal. Unique character at pyrolysis temperature of 400 °C. High adsorption removal capacity compared to other similar work. Removal of heavy metal by palm oil sludge biochar was dominated by chemical adsorption at monolayer.